INCREASING ADDED VALUE BY UTILIZING LOCAL POTENTIAL TO INCREASE COMMUNITY INCOME IN PELABUHAN DALAM VILLAGE - Bernadette Robini; Mukhlis Mukhlis; Deassy Apriani; Hamira Hamira (Jurnal Abdimas Indonesia, 2022)
The service of sriwijaya university assisted villages was carried out in the village of Pelabuhan Dalam, Pemulutan District, Ogan Ilir Regency, South Sumatra. This service aims to increase the income of rural communities, especially for housewives by utilizing local commodities, namely rice by processing them into food products that have a selling value so that they can create value-added which means income for all production factors used. The method used is the guidance and empowerment of the community towards the use value of rice commodity which is a local commodity that is widely produced in Pelabuhan Dalam Village. The result of this service activity is in the form of creating creativity and empowerment in making semprong cake with raw materials for rice flour. The existence of this activity, the village community can increase community knowledge.